A new patterning technique of membrane structures for minimizing deviations of stress and shape. (June 2020) - Yang, Yan; Qian, Sheng-shen; Gong, Jing-hai
Abstract: For cutting pattern generation of membrane structures, non-developability of doubly curved surfaces can cause deviations of stress and shape, which directly influence bearing capacity and structural integrity of final structures. Thus, cutting errors should be diminished as much as possible for precise-forming of membrane structures, especially for airships and air-supported structures as formwork. This paper proposes a new patterning technique to generate the optimized cutting pattern, which is based on a multi-objective optimization concept for simultaneously minimizing the deviations of stress and shape from design. Using the coordinates of 2D elements as key variables, the proposed method performs a geometrically nonlinear finite element analysis based on the initial cutting pattern iteratively. This approach can effectively reduce the deviations of stress and shape of the whole structure by reducing the stress deviation of 2D strips. The validity of the method is examined by the comparison of numerical results, which shows that the actual equilibrium stress is closer to design stress than that of existing works, and the shape distortion is almost negligible. Highlights: A precise patterning method for optimized cutting pattern generation. A multi-objective optimization concept for simultaneously minimizing the deviations of stress and shape from design. The independence of the proposed method to the geometry of initial cutting pattern. The effect of shear stiffness on cutting analysis.